PENGARUH ASPEK PENGALAMAN MEREK TERHADAP CUSTOMER DELIGHT PADA PENGGUNAAN KOSMETIK DEKORATIF KOREA - Adma Sari Sitepu (JURNAL LENTERA BISNIS, 2025)
The objective of this study is to examine direct impact of consumer brand experience through sensory, affective, behavioral and cognitive on the customer delight to use Korean decorative cosmetics. A survey-based data collection approach was employed, utilizing a questionnaire administered to 255 respondents in five region city of the Special Capital Territory of Jakarta. The data were analyzed using Multiple Regression Analysis. The findings indicate a positive effect of sensory and affective on the customer delight of usages of Korean decorative cosmetics. Additionally, the study reveals that the effect of behavioral and cognitive are not impactful on the customer delight . This research offers managerial insights, suggesting that marketers and stakeholders within the Indonesian cosmetics industry should develop marketing strategies that enhance consumers' emotions and foster positive attitudes toward the behavior of using Korean decorative cosmetics to incline further contributing to customer delight